Investigation of metallurgical and mechanical behavior of forged aluminium alloy hybrid composites. (2021) - Soundararajan, R.; Ramprakash, M.P.; Muthu Vel, T.J.; Ratteesh, M.; Puvanesh Kumar, S.
Abstract: The objective of this study was to fabricate Aluminium Alloy (AA8011) reinforcement such as 5 wt% of Zirconium Oxide (ZrO2 ) and 5 wt% of Aluminium Oxide (Al2 O3 ) particles were agitated by stir casting route and then strengthened through Uni-direction (X axis), Bi-direction (X & Y axis) and Multi-direction (X, Y & Z axis) forging routes. During the stir casting process, the ZrO2 and Al2 O3 reinforcements get incorporated within the matrix and are homogeneously dispersed to obtain Aluminum Matrix Hybrid Composites (AMHC). Further it was taken for uni, bi, multi - directional forging process, which enhances the mechanical and metallurgical behaviour of the Forged Aluminum Matrix Hybrid Composites (FAMHC). In which the mechanical properties like hardness, tensile and impact strength reveals that the multi-direction forged hybrid composite has preferably improved performance than the uni-directional and bi-directional forging. In metallurgical study the Scanning Electron Microscopy (SEM) revealed the homogeneous dispersion followed by the grain refinement of both the particles in the matrix and also it was evident from X-Ray Diffraction (XRD) analysis for the FAMHC samples. This technique also strengthens the hybrid composites due to equi-axial loading on the surface from three directions. On the whole, combined effect of addition of reinforcements through stir casting for fabricating the hybrid composites followed by multi– directional forging technique enhances the performance of the hybrid composite, thus making it a reliable alterative material for high strength applications in automobile and aeronautical industries.